Nigeria : Staff Report for the 2001 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Nigeria showed serious macroeconomic imbalances under the Stand-By Arrangement. Executive Directors observed that this had emerged as a result of the sharp increase in government spending, and expressed concern at the risks of a further acceleration of inflation and instability in the exchange market. They stressed the need to implement prudent fiscal and monetary policies for macroeconomic stability, and accelerate structural reforms. They called on Nigeria to show continued commitment toward a strong economic program that could be supported by the IMF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet